Dissertation Abstracts (Academy of Management Journal, 1962)
Presents abstracts of the studies which were published from 1960 to 1962. “Managerial Control in Selected Retail Appliance Businesses,” by Charles R. Klasson; “An Analysis and Evaluation of the Controllership Function and Training for Controllership Work,” by Clifford Edwin Hutton; “Managerial Manpower Planning in Selected Manufacturing Firms,” by Richard I. Hartman; “Moonlighting: An Analysis of Its Rational Practice and Possible Economic Implications,” by Leete A. Thompson.